1996
DOI: 10.1115/1.2822683
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Saturated Pool Boiling Heat Transfer From Smooth and Microporous Surfaces in FC-72

Abstract: The effects of surface treatments and " gassy-subcooling " on pool boiling heat transfer are quantified by testing both smooth and treated surfaces at gassy-subcooling levels from O°C to 40°C (1 arm) and 40°C to 85°C (3 atm). Incipient and nucleate boiling wall superheats decrease over this range of gassy-subcooling. At gassysubcooling levels greater than 20°C, the boiling curves for the smooth surface indicate two distinct regions governed by different heat transfer mechanisms, one in which the boiling proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 7 publications
4
17
1
Order By: Relevance
“…The pool boiling data are obtained from our previously published work (Wei and Honda 2003). Both the flow and pool boiling curves of the smooth surfaces of O'Connor et al (1996) and Rainey et al (2001) agree well with those of chip S except for a lower CHF value due to the lower liquid subcooling. For the flow boiling case, the single-phase, forced convection curves for the micro-pin-finned surfaces show much higher heat flux than those for the smooth surface due to the total surface increase, and increase with the total surface area in the order of chips S, PF30-60, PF30-120, indicating that the side walls of the micro-pin-fins are exposed to the fluid flow and are active for the forced convection heat transfer.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The pool boiling data are obtained from our previously published work (Wei and Honda 2003). Both the flow and pool boiling curves of the smooth surfaces of O'Connor et al (1996) and Rainey et al (2001) agree well with those of chip S except for a lower CHF value due to the lower liquid subcooling. For the flow boiling case, the single-phase, forced convection curves for the micro-pin-finned surfaces show much higher heat flux than those for the smooth surface due to the total surface increase, and increase with the total surface area in the order of chips S, PF30-60, PF30-120, indicating that the side walls of the micro-pin-fins are exposed to the fluid flow and are active for the forced convection heat transfer.…”
Section: Resultssupporting
confidence: 58%
“…), and copper particle (3-10 μm in dia.) (O'Connor et al , 1996Chang and You 1996), porous metallic matrix surface by brazing metal powder to the base surface (50-60% void fraction) (Bergles and Chyu 1982). All above treated surfaces experienced the drawback of severely deterioration of boiling heat transfer at the high heat flux region and the wall temperature at the critical heat flux (CHF) is larger than the upper limit for the reliable operation of LSI chips, 85…”
Section: Introductionmentioning
confidence: 99%
“…10. The boiling curves of the microporous surface developed by O'Connor et al (1996) and a smooth surface are also shown for comparison. The test surface of O'Connor et al (1996) had a porous layer consisting of 8-12 μm diamond particles produced by painting technique.…”
Section: Pool Boiling Performance Of Micro-pin-finned Surfacesmentioning
confidence: 99%
“…The boiling curves of the microporous surface developed by O'Connor et al (1996) and a smooth surface are also shown for comparison. The test surface of O'Connor et al (1996) had a porous layer consisting of 8-12 μm diamond particles produced by painting technique. The porous surface shows a severe deterioration of boiling heat transfer performance at high heat flux region and the value of q CHF is smaller than that of the micro-pin-finned chips.…”
Section: Pool Boiling Performance Of Micro-pin-finned Surfacesmentioning
confidence: 99%
See 1 more Smart Citation